2004
DOI: 10.1038/sj.ejcn.1601930
|View full text |Cite
|
Sign up to set email alerts
|

Short-term digestive tolerance of different doses of NUTRIOSE®FB, a food dextrin, in adult men

Abstract: Objective: To determine the tolerance of increasing dosages of an incompletely hydrolysed and/or incompletely absorbed food dextrin coming from wheat starch, NUTRIOSE s FB, at daily levels of 10 and 15 g up to 60 and 80 g, respectively. Design: A randomized, double-blind, multiple dose, placebo-controlled, combined crossover and parallel trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…The effect of RS on fecal output has been mixed and may depend on the physicochemical properties of the specific RSs. High doses of wheat dextrin (up to 80 g/day) had only a minimal effect on fecal output [13] , while another study with lower doses of RS2 and RS3 (30 g/day) showed that both altered fecal weight in healthy humans [14] . Retrograded maltodextrin (40-60 g/day) administered for 21 days produced an increase in total bowel movements and frequency of watery feces [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of RS on fecal output has been mixed and may depend on the physicochemical properties of the specific RSs. High doses of wheat dextrin (up to 80 g/day) had only a minimal effect on fecal output [13] , while another study with lower doses of RS2 and RS3 (30 g/day) showed that both altered fecal weight in healthy humans [14] . Retrograded maltodextrin (40-60 g/day) administered for 21 days produced an increase in total bowel movements and frequency of watery feces [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Most trials administer either fructo-oligosaccharides or inulin, compared with a maltodextrin control; seven trials administer doses between 10-18g/day (Pedersen et al, 1997;Davidson et al, 1998;Letexier et al, 2003;Cani et al, 2006;Forcheron & Beylot, 2007;Genta et al, 2009;Cani et al, 2009), two trials administer doses of 20-21g/day (Luo et al, 1996;Parnell & Reimer, 2009). Two trials administer a modified dextrin in a dose-response manner at doses of 30, 40, 60 or 80 g/day (Van den Heuvel et al, 2004;Pasman et al, 2006) 9.11. No significant effect of non-digestible oligosaccharide or inulin supplementation and energy intake is demonstrated (-378kJ, 95% CI -791, 36kJ; p=0.07).…”
Section: Non-digestible Oligosaccharides and Fasting Ldl-cholesterol mentioning
confidence: 99%
“…Eleven randomised controlled trials in adults were identified that presented evidence on non-digestible oligosaccharide or inulin supplementation and energy intake, eight of which were included in a meta-analysis (Luo et al, 1996;Pedersen et al, 1997;Davidson et al, 1998;Cani et al, 2006;Pasman et al, 2006;Forcheron & Beylot, 2007;Cani et al, 2009;Parnell & Reimer, 2009). Three trials could not be included in a meta-analysis as they did not report the necessary data (Letexier et al, 2003;Van den Heuvel et al, 2004;Genta et al, 2009)(Cardio-metabolic review, Energy Intake and Eating Motivation review, p115-118).…”
Section: Non-digestible Oligosaccharides and Fasting Ldl-cholesterol mentioning
confidence: 99%
“…Very well tolerated, Nutriose may be 20-25% of a product's composition without causing discomfort or bloating. About 15% of Nutriose are absorbed in the small intestine, about 75% fermented in the large intestine, while the remainder (about 10%) is excreted in the faeces [72,110]. Nutriose induced an increase of the colonic saccharolytic flora and decrease in potentially harmful Clostridium perfringens in human faeces [54,72].…”
Section: Prebiotic Effects Of Resistant Starch and Resistant Dextrinmentioning
confidence: 99%
“…Nutriose induced an increase of the colonic saccharolytic flora and decrease in potentially harmful Clostridium perfringens in human faeces [54,72]. Nutriose induced a decrease in the faecal pH of human volunteers, increased production of short chain fatty acids (SCFAs) in rats [54], induced changes in faecal bacterial enzyme concentration [72,110]. It was also shown that learning (respectively physical) performances are improved in rats 180 minutes (respectively 150 minutes) after the consumption of Nutriose, compared to dextrose.…”
Section: Prebiotic Effects Of Resistant Starch and Resistant Dextrinmentioning
confidence: 99%